Pogodda, S., Richmond, O.P. y Visoka, G. (2023). Failed Peacemaking: Counter-Peace and International Order. Springer Nature, 127 pp. - García Bartolomé, Gonzalo (Relaciones Internacionales, 2024)
Reseña de: Pogodda, S., Richmond, O.P. y Visoka, G. (2023). Failed Peacemaking: Counter-Peace and International Order. Springer Nature, 127 pp.